Home range size of Tengmalm’s owl offspring during the post-fledging dependence period in Central and North Europe - Stehlíková Sovadinová, Simona; Kouba, Marek; Ševčík, Michal; Tulis, Filip; Bušina, Tomáš; Korpimäki, Erkki (Frontiers in Ecology and Evolution, 2024)
A greater knowledge of the intrinsic and extrinsic factors of animal home range (HR) formation can help us to understand the fundamental biological issues underlying, for instance, movement patterns, habitat selection and survival. However, very little is known about the HRs of birds of prey fledglings, even though the post-fledging phase is recognised as crucial due to the high mortality of juvenile birds. We radio-tracked 138 Tengmalm's owl (Aegolius funereus) fledglings from 43 broods to determine their HRs during the post-fledging dependence period and to investigate the factors affecting their sizes. The study was conducted during four breeding seasons in Czechia and two seasons in Finland. The mean fledglings' HR size calculated according to the 95% IID Kernel Density Estimation method was 63.7 ± 43.9 ha (± SD; n = 71) during nocturnal activity and 52.0 ± 46.1 ha (n = 63) during diurnal roosting. The sizes of both nocturnal activity and diurnal roosting HRs increased with the longer individual duration of the post-fledging dependence period and also the higher rank of hatching within a brood. Diurnal roosting HRs were two times smaller in the Czech site, probably because of the very limited number of dense forest patches suitable for roosting as a legacy of the air pollution calamity in the 1970s, during which most coniferous stands died out. There was no difference in the size of nocturnal activity HR between the two study areas, although they differed markedly in terms of night length, altitude, weather, and forest age, structure and composition. This suggests that environmental factors are not decisive in determining the size of nocturnal activity HRs of Tengmalm's owl fledglings. Since the diurnal HRs always occurred within the area of the nocturnal HRs, we suggest that conservation of the densest and preferably oldest forest stands within the areas of the study species occurrence may offer straightforward conservation tasks for protecting Tengmalm's owl fledglings and also other species.